Heart of darkness : authoritative text, backgrounds and contexts, criticism - Conrad, Joseph, 1857-1924 (Norton critical edition., 2017)
"Heart of Darkness follows the story of Charlie Marlow's time working on the Congo River. In his attempts to aid Mr. Kurtz, the chief of the Inner Station, Marlow is confronted with the cruel realities of European imperialism in Africa. This Norton Critical Edition is based on the 1902 English first book publication. The text comes paired with explanatory footnotes, illustrations and photographs, and an introduction by the editor. "Backgrounds and Contexts" explores the wide range of historical attitudes that influenced the text, including essays on imperialism and the Congo, Nineteenth-Century Attitudes Toward Race, Conrad in the Congo, and The Author on Art and Literature. "Criticism" examines a wide range of critical responses to the novella, which span from Conrad's peers up until the twenty-first century. Essays from Chinua Achebe, Jeremy Hawthorn, Hunt Hawkins, Ian Watts, J. Hillis Miller, and others have been carried over from the previous edition. These classic essays are further supported by new material from Benita Parry, Susan Jones, Richard J. Ruppel, Adriana Cavarero, Jeffrey Mathes McCarthy, Urmila Seshagirl, and Nidesh Lawtoo. The collection of essays on film adaptations of the novella has been completely revised to include essays by Robert L. Carringer, Seymour Chatman, and Pamela Demory. A Chronology and revised Selected Bibliography are also included."--